2023
DOI: 10.1021/acsnano.3c03605
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Solution Patterning for Two-Dimensional Perovskite Nanoplate Arrays

Abstract: Two-dimensional perovskite crystals have attracted significant attention for their diverse optoelectronic characteristics, owing to their superior semiconducting properties. However, the majority of studies to date have focused on single crystals, which pose challenges for integration into device arrays due to their incompatibility with selective growth or conventional lithography techniques. Here, a facile one-step solution process for synthesizing 2D perovskite crystal arrays is proposed through meniscus-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 48 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…[1][2][3][4] Particularly, the intrinsic advantages of their hybrid semiconductor properties, such as high photoluminescence quantum yield, narrow emission linewidth, high optical gain performance, long-distance bipolar carrier diffusion, high defect tolerance and easily tunable optical bandgap, ensure that the perovskites films act as a promising coherent light source and versatile candidate for developing high-performance solutionprocessed lasers. [5,6] The perovskite materials with various morphologies containing nanocrystals, [7] nanowires, [8] polycrystalline thin films, [9] nanoplates [10] and spherical resonators [11] can present the stimulated emission, and can be used as an optical gain medium in the visible and nearinfrared spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Particularly, the intrinsic advantages of their hybrid semiconductor properties, such as high photoluminescence quantum yield, narrow emission linewidth, high optical gain performance, long-distance bipolar carrier diffusion, high defect tolerance and easily tunable optical bandgap, ensure that the perovskites films act as a promising coherent light source and versatile candidate for developing high-performance solutionprocessed lasers. [5,6] The perovskite materials with various morphologies containing nanocrystals, [7] nanowires, [8] polycrystalline thin films, [9] nanoplates [10] and spherical resonators [11] can present the stimulated emission, and can be used as an optical gain medium in the visible and nearinfrared spectra.…”
Section: Introductionmentioning
confidence: 99%
“…[ 7 ] More recently this approach was extended for the core‐shell growth of Pb‐based 2DLPs and Pb‐free layered double perovskites and scaled up by employing a solution shearing process. [ 8,9 ] The sequential crystallization relies heavily on the different solubility of the 2DLPs in the respective quaternary solvent system. Therefore precise fine‐tuning is key to maintain the overall structure of the 2DLP.…”
Section: Introductionmentioning
confidence: 99%
“…Organic semiconductors, quantum dot (QD) solids, and other partly ordered condensed matter systems are actively studied as promising materials for solar energy, light-emitting, and other optoelectronic devices. Transport of both charge and excitation has a large effect on the performance of such devices. Despite the differences in chemical composition, it has been shown that, from the point of view of transport, disordered organic semiconductors and QD solids have much in common: energetic disorder can lead to localization of electron and hole states and, consequently, to the hopping transport mechanism. , It is known that spatial-energy correlations significantly affect transport in organic semiconductors, especially materials composed of molecules with large dipole moments, when the correlations are the most long-range (dipole glasses). , Typically, hopping transport in materials with correlated disorder is modeled by numerical Monte Carlo (MC) methods, , but recently an analytic approach has been developed .…”
mentioning
confidence: 99%